Evaluation of the Genetically Diagnosed Mitochondrial Disease Cases with Neuromuscular Involvement - Çağatay Günay; Cem Paketçi; Pınar Edem; Gamze Sarıkaya Uzan; Ayşe Semra Hız Kurul; Zümrüt Arslan Gülten; Pelin Teke Kısa; Nur Arslan; Uluç Yıs (Galenos Publishing House, 2022)
Objective: Due to the fact that mitochondrial diseases can involve different organ systems, neuromuscular involvement is frequently observed and has a substantial place in clinical practice. In this study, the clinical, radiological, electrophysiological and imaging features of the patients with mitochondrial disease with neuromuscular involvement were investigated. Method: The clinical, radiological and genetic features of 16 patients with genetically diagnosed mitochondrial disease followed in the Departments of Pediatric Neurology and Pediatric Metabolism and Nutrition in Dokuz Eylül University Faculty of Medicine were retrospectively evaluated. Results: The cases were between 3-17 years of age (mean: 8.8+-4.2 years). 44% (n=7) of the cases were male. Clinical findings started at a mean age of 30 months (2-132 months). There was consanguineous marriage in 81% (n=13) of the cases. Leigh syndrome (LS), Charcot-Marie-Tooth disease (CMT) 2A, and CMT disease-axonal-type 2K were diagnosed in 5, 4, 2 cases, respectively. Alpers syndrome, combined oxidative phosphorylation deficiency-13, megalencephaly without cystic leukoencephalopathy, mt.9804G>A and m.11696G>A mutations which could not be phenotyped syndromicly were detected in one case each. SURF1 (n=2), MTATP6 (n=2) and PDSS2 (n=1) mutations were found in the patients with LS. NARS2, PNPT1, and RNASET2 mutations were found in the patients with Alpers syndrome, combined oxidative phosphorylation deficiency-13, cystic leukoencephalopathy without megalencephaly, respectively. Muscle weakness, developmental delay and skeletal deformity were the most common findings. The most common finding in brain magnetic resonance imaging was increased T2 signal in bilateral basal ganglia. Conclusion: The most common genetically diagnosed mitochondrial disease was LS, the most common mutation was MFN2, and the most common clinical finding was muscle weakness.